Development and characterization of value-added cookies rich in vitamin D and calcium by incorporating eggshell powder and cod liver oil - Qureshi, Aneela; Siddique, Farzana; Arshad, Muhammad; Hussain, Ashiq; Zia, Muhammad; Siddique Raza, Muhammad; Bilal, Muhammad; Xin, Zou; Aziz, Tariq; Al-Hoshani, Nawal; Al-Asmari, Fahad; Al-Joufi, Fakhria (Italian Journal of Food Science, 2025)
Eggshell powder (ESP), because of its high bioavailability and low cost, can be added to the diet as an extra source of calcium. Similarly, cod liver oil (CLO), being a good source of vitamin D and omega 3 fatty acids, is a good choice to replace conventional shortenings in bakery products. Therefore, the goal of the current study was to valorize eggshell waste by adding ESP to the cookies that also contain CLO. Nutritional, physical, and sensory qualities of developed cookies were examined, with a focus on calcium and vitamin D contents. Comparative nutritional analysis of ESP and commercial straight grade flour (CSGF) revealed higher nutritional content in ESP, while CLO was determined to be a good source of polyunsaturated fatty acids and vitamin D. Nonsignificant results were reached regarding the weight, width, thickness, and spread factor of different treatments on cookies. The incorporation of ESP and CLO significantly (p ≤ 0.05) increased the protein, fat, fiber, and ash contents of cookies. Further results showed that the calcium content of cookies was increased from 972 mg to 1732 mg with different treatments. The vitamin D content of cookies was also significantly (p ≤ 0.05) improved from 588 IU to 1,684 IU with different treatments. Fourier transform infrared spectroscopy and X-ray diffraction analyses of the cookies  confirmed the higher proportion of calcium and vitamin D in supplemented cookies. The sensory eval-uation of cookies revealed that incorporation of up to 3 g of ESP and 9.6 mL of CLO as replacements of CSGF and shortening, respectively, was established as acceptable for the development of good-quality cookies, which although obtained lesser but very comparative sensory scores to the control, leading to consumer satisfaction. Thus, ESP and CLO could be used to develop nutritional bakery products having high contents of vitamin D and calcium.